Effect Of The Covid 19 Pandemic On Smoking Behavior: Library Study - Devi Isnaini, Aulia (Riviera Publishing, 2022)
Covid-19 is an infectious disease that attacks the respiratory system. A person who smokes will be more susceptible to contracting Covid-19 due to a decrease in lung function caused by prolonged smoking activity. Studies in some cases have shown a negative correlation between Covid-19 and cigarettes, where smokers will have a higher risk of Covid-19 severity than nonsmokers. Some research results reveal that during the Covid-19 pandemic there was a mixed reaction from smokers. Some smokers decided to quit smoking after the Covid-19 pandemic based on personal awareness about the adverse effects of smoking, especially at this time. While not a few people increase cigarette consumption. This happens due to various factors, one of which is due to a lack of public knowledge of the adverse effects of smoking. So that there is a need for public awareness of the importance of a healthy lifestyle by stopping or reducing smoking